2015
DOI: 10.1111/jmi.12213
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional morphological modelling of concrete using multiscale Poisson polyhedra

Abstract: This paper aims at developing a random morphological model for concrete microstructures. A 3D image of concrete is obtained by microtomography and is used in conjunction with the concrete formulation to build and validate the model through morphological measurements. The morphological model is made up of two phases, corresponding to the matrix, or cement paste and to the aggregates. The set of aggregates in the sample is modelled as a combination of Poisson polyhedra of different scales. An algorithm is introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Numerical simulations showed that the realistic shape of cement particles influences the (simulated) rate of hydration, percolation threshold, early age E modulus and rheology properties [11]. Implementing the realistic cement particle shape [35] (similarly as it is done for aggregates in concrete [9,10,36]), and therefore realistic heterogeneity of the cement paste in micromechanical and microstructure models, is very important for any kind of study on cement paste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations showed that the realistic shape of cement particles influences the (simulated) rate of hydration, percolation threshold, early age E modulus and rheology properties [11]. Implementing the realistic cement particle shape [35] (similarly as it is done for aggregates in concrete [9,10,36]), and therefore realistic heterogeneity of the cement paste in micromechanical and microstructure models, is very important for any kind of study on cement paste.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a step further was made with particle shape models for concrete and mortar. In such models, the irregular shape of aggregate particles is taken into account, resulting in a more realistic material structure [9,10]. Including realistic shapes of cement particles in hydration models is, however, non-trivial, as the particle shape influences the cement hydration [11].…”
Section: Introductionsmentioning
confidence: 99%
“…In Moreaud et al (2012), a hardcore deposit model is proposed to simulate a boehmite material. However, the simulation of microstructures using hardcore models becomes difficult when approaching the close-packing limit (Escoda et al, 2015). To overcome this difficulty, random walk stochastic procedures have been developed (Altendorf and Jeulin, 2011) to generate fibrous microstructures, as an improvement on random sequential adsorption models (Feder, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…As touching particles are frequently observed in our samples, we use a variant of the algorithm discussed in Escoda et al . () for modelling particles in concrete. The model is obtained in the following way: For n=0, start with an empty window W and insert a random polyhedron p 0 at a random location. Increase n by 1 and suggest to insert a random polyhedron pn at a random location in W .In case pn intersects any previously placed polyhedron pm, 0m<n, move pn in a random direction.…”
Section: Modelmentioning
confidence: 99%
“…The method is easy to implement and was also used in Zhang et al (2014) for selecting the random position of reinforcement particles in an MMC. As touching particles are frequently observed in our samples, we use a variant of the algorithm discussed in Escoda et al (2015) for modelling particles in concrete. The model is obtained in the following way:…”
Section: Fitting Of Particle Volume and Elongationmentioning
confidence: 99%